China as a ‘systemic challenge’ for NATO strategic interests - O. A. Timakova (Проблемы постсоветского пространства, 2024)
NATO’s 2022 Strategic Concept views China as a “systemic challenge” to the Alliance. Joint statements regarding China began to appear several years before the adoption of the new Concept on the official NATO agenda in response to increasing pressure from the Trump administration. The military-political, technological and discursive power of the PRC is perceived by the bloc as a threat to their strategic interests. The greater military-political presence of China in the Arctic and in the Middle East and North Africa is regarded by NATO countries as strengthening the hegemonic aspirations of the PRC. Technological dependence on supplies from China harms the Alliance’s operational capabilities and military mobility. NATO has set itself the goal of adapting to strategic competition with China, particularly in the areas of advanced technologies, artificial intelligence and 5G. China’s influence on the media agenda, as well as its ability to promote its own narrative, threatens transatlantic solidarity and the “soft power” of the Alliance countries. Moreover, China is accused of systematically seeking to sow divisions in transatlantic relations and exploit differences between Western countries to its own advantage. China’s efforts to forge a multipolar world order pose a direct challenge to Western liberal democracies and the rules-based international order. European NATO states have begun to regularly encounter the “China factor” when interacting with the United States. However, there remains disagreement over what policies should be pursued toward Beijing. Those who see China as a security threat advocate general policy coordination with the United States. Those who recognize Beijing as a necessary economic partner and participant in global governance insist that Europe pursue independent policies that distance itself from US strategy. All this suggests that practical steps within the Alliance to counter China, especially outside the Euro-Atlantic region, will face resistance from the United States’ European allies.